The modernist novel and the decline of empire - Marx, John (Cambridge University Press, 2005)
John Marx argues that the early twentieth century was a key moment in the emergence of modern globalization, not simply a period of imperial decline. Rather than mapping the Empire's end, modernists including Conrad and Woolf celebrated the shared culture of English rather than the waning imperial structures of Britain.